Distribution System and Fulfillment of Clean Water Needs in Lonthoir Village, Banda District, Central Maluku Regency - Fakir, Fatma; Salakory, Melianus; Partini, Dwi (Jurnal Pendidikan Geografi Unpatti, 2023)
Distribution System and Fulfillment of Clean Water Needs in Lonthoir Village, Banda Sub-district, Central Maluku Regency, with a pipeline network only in a few houses, so many residents still need a clean water network. In addition, the quality of the existing water network is still being determined. This study aims to determine the distribution system and fulfillment of clean water needs in Lonthoir Village, Central Maluku District. The type of research used is descriptive-analytic using a cross-sectional design, with two research samples, namely water samples (reservoir basins and community basins) and community samples (consisting of 10 respondents). The results showed that in Lonthoir Village, one of the things that made the water distribution system less fulfilled was the reservoir tub was only 5x6. The pipe used to be estimated from the broncaptering to the reservoir tub was still using a 5-inch pipe, and from the reservoir tub to the community, the pipe used was the same. Fulfillment of clean water needs is less fulfilled if water is distributed from the reservoir. The flowing water still uses gravity to slow down water distribution to the community, while the water demand for the community is >200 L / day. In addition, the lab test results for the two existing water samples contained one indicator of the chemical parameters that did not meet the maximum quality standards and the requirements of PERMENKES No. 32 of 2017, namely the pH indicator element.